Unpredictable cycloisomerization of 1,11-dien-6-ynes by a common cobalt catalyst - Suleymanov, Abdusalom A.; Vasilyev, Dmitry V.; Novikov, Valentin V.; Nelyubina, Yulia V.; Perekalin, Dmitry S. (Beilstein Journal of Organic Chemistry, 2017)
1,11-Dien-6-ynes undergo cycloisomerization in the presence of the cobalt catalytic system CoBr2/phosphine ligand/Zn/ZnI2 giving cyclohexene, diene or cyclopropane structures depending on the type of the phosphine ligand. This unpredictable behaviour suggests that, although the availability of the cobalt catalytic system is appealing, the development of well-defined catalysts is desirable for further progress.
Keywords: catalysis; cobalt; cyclization; enynes; ligands